Manajemen Komunikasi dan Negosiasi Pendidikan Islam Multikultural di Indonesia - Nurmala Sari, Tanti; Normuslim; Muslimah (PAI RAFAH, 2025)
Communication and negotiation management play a crucial role in fostering an inclusive Islamic education environment within Indonesia's culturally and religiously diverse society. This study aims to critically analyze communication and negotiation strategies that are specifically applied in managing multicultural dynamics within Islamic educational settings in Indonesia. Employing a structured literature review method, the study synthesizes findings from peer-reviewed journals and scholarly articles selected based on relevance to multicultural education, communication theory, and Islamic pedagogical practices. The analysis reveals key strategies including the dissemination of accurate intercultural information, stakeholder collaboration across religious and ethnic lines, and the promotion of media literacy to combat stereotypes and prevent social polarization. It also highlights contextual challenges such as socio-cultural resistance, inconsistent policy frameworks, and the influence of global narratives on Islamic identity. This article contributes to the discourse on Islamic education by offering a framework for culturally responsive communication and negotiation practices, relevant to practitioners and policymakers aiming to strengthen multicultural harmony through education in Indonesia.